2016
DOI: 10.3892/mmr.2016.5789
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective potential of Dendrobium officinale Kimura et Migo against myocardial ischemia in mice

Abstract: Dendrobium officinale Kimura et Migo has been used for thousands of years to promote body fluid production; however, little is currently known regarding its effects on the heart. The present study aimed to explore the cardioprotective potential of the water extract of Dendrobium officinale Kimura et Migo (DOE) on myocardial ischemia in mice. A mouse model of myocardial ischemia was induced following ligation of the left anterior descending coronary artery. Prior to the operation, mice were administered a vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Our data suggested that FWEP could be an effective electron donor capable of reacting with free radicals to convert them into more stable products . According to Dou et al, the cardio‐protective potential induced by polysaccharide against myocardial ischemia injury could be explained by the ligation of the left anterior descending coronary artery associated with antioxidant enzyme activity restoration and apoptosis inhibition.…”
Section: Discussionmentioning
confidence: 62%
“…Our data suggested that FWEP could be an effective electron donor capable of reacting with free radicals to convert them into more stable products . According to Dou et al, the cardio‐protective potential induced by polysaccharide against myocardial ischemia injury could be explained by the ligation of the left anterior descending coronary artery associated with antioxidant enzyme activity restoration and apoptosis inhibition.…”
Section: Discussionmentioning
confidence: 62%
“…One study indicated that D. officinale water-soluble extracts prevented diabetic cardiomyopathy and might be a candidate for therapeutic use (Zhang et al, 2016). D. officinale water extracts (75, 150, and 300 mg/kg) intragastrically once daily for 2 weeks could protect left anterior descending coronary artery (LAD)-induced myocardial ischemia through decreasing creatine kinase (CK)-MB, lactate dehydrogenase (LDH), malondialdehyde (MDA), and increasing superoxide dismutase (SOD) and Meis 1 levels (Dou et al, 2016). Treatment with D. officinale stems polysaccharide DOP-GY at the doses of 6.25, 12.5, and 25 µg/ ml exhibited protective effects on hydrogen peroxide (H 2 O 2 )induced H9c2 cardiomyocyte apoptosis via phosphatidylinositol/ protein kinase B (PI3K)/Akt and mitogen-activited protein kinase (MAPK) signaling pathways, as demonstrated by the decreased levels of LDH, lipid peroxidation damage (LPD), reactive oxygen species (ROS), and pro-apoptosis protein (Zhang et al, 2017a).…”
Section: Cardioprotective Activitymentioning
confidence: 99%
“…Evidence suggests that oxidative stress is involved in myocardial ischemia and that antioxidant treatment may be beneficial in cardiac damage during ischemia (7)(8)(9). Markers of oxidative stress, including reactive oxygen species (ROS), malondialdehyde (MDA) and superoxide dismutase (SOD), are frequently used to monitor mitochondrial oxidative damage (10,11). Furthermore, it has been demonstrated that apoptosis serves an important role in ischemic-hypoxic myocardial injury (12,13); when the mitochondrial membrane potential is lost, the process of apoptosis is activated, leading to cell death (14).…”
Section: Introductionmentioning
confidence: 99%